EXPLORING THE INTRICATE ARCHITECTURAL FABRIC OF A HISTORIC ARAB MEDINA: A STUDY OF NABLUS OLD TOWN - Abdalrahman Kittana; Ameen Abu-baker (Journal of Islamic Architecture, 2023)
Scholars have been fascinated with the complex and intricate urban structure within Islamic cities. Over the years, they have used various terms and designations, such as labyrinthine, maze-like, spontaneous, organic, and similar descriptors, to characterize this intricate nature. However, these terms often suggest a lack of order or systematic organization, which limits our understanding of how urban spaces were created and regulated, especially at the micro-level of city development. This essay seeks to provide a case-based insight into the processes of creating, adapting, and managing spaces in pre-modern Islamic cities by examining original archival documents from the Ottoman period. The study concludes that the dynamic character of the decision-making process, influenced by a framework for decision and counterbalancing practices and amplified by the ability to divide the entire structure or building into components that can be interchanged with neighboring elements, opened the door to a limitless range of spatial arrangements that led to the emergence of complex interconnections and apparent irregularities.